Hygienic practices and microbial contamination of small-scale poultry slaughter houses at peri-urban areas of Hanoi, Vietnam - Nguyen Viet Khong; Pham Thi Ngoc; Dinh Xuan Tung; Lapar, Ma. Lucila; Unger, Fred; Hung Nguyen-Viet; Phuc Pham Duc; Pham Thi Nga; Gilbert, Jeffrey (2012)
To understand the overall of current veterinary hygiene situation concerning microbiological contamination of food, we have conducted a survey, interview, collecting and analyzing samples derived from poultry (alive and carcasses), slaughter environment of 36 small slaughter houses in the rural area of Hanoi. Almost all small slaughter houses (98% indoor and 100% at the bazaars/day-market) in the lowest veterinary ranking according to the government criteria. The rate of Salmonella contamination was 29.2% for the cloacal swab, 40.6% for carcasses, 2.9% for rinse water, 80.6% for waste water, 30.6% for slaughter floor and 63.9% for tools. Among the isolates from the most noticeable contamination carcasses, it was important to note that there were present of 2 serotype (S.enteritidis and S.typhimurium) that belong to the high risk group of food poisoning, originated from poultry during slaughtering processes. The Salmonella isolates had the antimicrobial resistance properties to most common antimicrobials, readily spreading along with the poultry meat chain. Water source and waste were both the highest risk factors leading to the Salmonella contamination for carcasses. There were two main recommendations to improve the hygiene condition at the time being, which were (i) to make awareness of high risk of bacterial contamination to the owners and butchers, (ii) improve the quality of water source as well as the waste treatment.